Potensi Daun Alpukat Sebagai Antibakteri - Irna Wijaya (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Excessive microorganisms can disturb the body's balance and cause infection. Infectious disease is a major health problem that occurs in several countries, especially Indonesia. Antibiotics are the main drug of choice used in dealing with infectious diseases. Irrational use of antibiotics can cause antibiotic resistance problems. This causes people to choose alternative or traditional medicine as a treatment for infectious diseases. One type of plant that can be used as traditional medicine is the Avocado Plant (Persea Americana Mill). Avocado plant parts that can be used as medicine are avocado leaves. The existence of secondary metabolites, namely alkaloids, flavonoids, tannins, and saponins on avocado leaves can inhibit the growth of bacteria (antibacterial) Objective: find out more about the potential of avocado leaves as an antibacterial. Method: The method used by the author is the study of literature from various national and international journals. This method is used with the aim of presenting, increasing knowledge and understanding of the topics covered by summarizing the material that has been published and providing information on facts or new analysis from the review of relevant literature then comparing the results in the article. Results: Avocado leaves have the ability to inhibit the growth of bacteria (antibacterial). Conclusion: Avocado (Persea Americana mill) leaves have potential as an antibacterial. That is because of the content of secondary metabolites found in avocado leaves. Secondary metabolites that have mechanisms to inhibit bacteria on avocado leaves are flavonoids, alkaloids, tannins, and questions